The role of Annexin A3 in coronary arterial lesions in children with Kawasaki disease - Li, Mengling; Liu, Dong; Jing, Fengchuan; Liu, Ruixi; Yi, Qijian (Frontiers in Pediatrics, 2023)
Kawasaki disease (KD) is an acute, self-limited vasculitis, and the etiology is still unclear. Coronary arterial lesions (CALs) are a major complication of KD. Excessive inflammation and immunologic abnormities are involved in the pathogenesis of KD and CALs. Annexin A3 (ANXA3) plays crucial roles in cell migration and differentiation, inflammation, cardiovascular and membrane metabolic diseases. The purpose of this study was to investigate the effect of ANXA3 on the pathogenesis of KD and CALs. There were 109 children with KD in the KD group (which was divided into two groups: 67 patients with CALs in the KD-CAL group, and 42 patients with noncoronary arterial lesions (NCALs) in the KD-NCAL group) and 58 healthy children in the control (HC) group. Clinical and laboratory data were retrospectively collected from all patients with KD. The serum concentration of ANXA3 was measured by enzyme-linked immunosorbent assays (ELISAs). Serum ANXA3 levels were higher in the KD group than in the HC group (P<0.05). There was a higher concentration of serum ANXA3 in the KD-CAL group than in the KD-NCAL group (P<0.05). Neutrophil cell counts and serum ANXA3 levels were higher in the KD group than in the HC group (P<0.05) and quickly decreased when the patients were treated with IVIG after 7 days of illness. Platelet (PLT) counts and ANXA3 levels concurrently exhibited significant increases 7 days after onset. Furthermore, ANXA3 levels were positively correlated with lymphocyte and PLT counts in the KD and KD-CAL groups. ANXA3 may be involved in the pathogenesis of KD and CALs.